The Deportation of Juan: Migration Rhetoric as Decolonial Strategy in Revelation - Mata, Roberto (Open theology, 2021)
This article explores John’s Exodus rhetoric as a decolonial strategy and maps its implications for contemporary migrants. Other scholars have convincingly argued that local authorities deported John to Patmos as a vagus , because his message opposed civic institutions, but they do not explain the nature and function of his preaching. Using migrant narratives and decolonial theory, I read John’s call to come out of Babylon and his deployment of Exodus topoi as migration rhetoric. He uses topoi of liberation, wilderness wanderings, and promised land to subvert the colonial situation of the assemblies under Rome. Rather than migrating to a place, believers embody the eschatological Exodus by rejecting food offered to idols and upholding the boundaries of Jewish identity as they wait for the full realization of God’s kingdom in the New Jerusalem. Regarding Latinx migrant communities, John’s Exodus rhetoric informs how migrants legitimate their migration and how they negotiate identity and resist imperialism in the US/Mexico borderlands.